PENGELOLAAN PROGRAM KELAS IDAMAN (UNGGULAN) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH MENENGAH ATAS (SMA) AN-NUR II BULULAWANG KABUPATEN MALANG - Dinda Utama Putri; Masykuri Bakri; Mutiara Sari Dewi (VICRATINA, 2020)
The role of education is pervasively important, particularly in preparing the human resources who are qualified, honest, competent, and creative as well as having a high professionalism. Excellent class is a superior class which has a variety of intra and extracurricular activities to support the learning process that aims to enhance students’ learning outcomes both in the cognitive, affective and psychomotor domains. In case of classroom facilities, excellent class is truly different from regular class. In this research study, the researchers are the main instrument as well as becoming the participant observers. In collecting data, researchers applied some research methods namely observation, interviews and documentation in order to obtain accurate results. The results of this study indicated that the planning of excellent classroom management programs in improving students’ learning outcomes in Islamic religious education (PAI) subjects at An-Nur Bululawang High School in Malang have 4 plans which are the input of students in excellent class, excellent homeroom teacher, excellent class curriculum and learning atmosphere. Then, the implementation includes learning process of excellent class, learning program of excellent class, and evaluation of students’ learning outcomes of excellent class. To conclude, teaching and learning models of excellent class are discovery learning, inquiry learning, problem based learning and project based learning.